Aktualisasi Kedudukan Hukum Islam dalam Perspektif Hukum Nasional Indonesia - Nabilah Apriani (Jurnal Hukum Lex Generalis, 2022)
Rigid and non-flexible laws will lead to complex conflicts. So that a legal system is needed whose existence can be accepted by the community. This research focuses on how Islamic Law is positioned in the perspective of Indonesian national law as well as how the application of Islamic Law in Indonesia. This research uses normative juridical approach methods by conducting a comprehensive review of theories, concepts and laws and regulations to find answers to problems in research. Thus resulted in a conclusion that the position of Islamic Law in Indonesia has been in line with the philosophical-political, juridical, and sociological order. Although its implementation still finds obstacles, Islamic law has succeeded in contributing to the establishment of national law. This is evidenced by the formulation of Islamic Law into several products of Indonesian laws and regulations.